Arithmetic About Recursion

Let k 1 , k 2 , , k_1, k_2, \ldots, be a sequence that is recursively defined as k n + 2 = k n + 1 + 2 k n k_{n+2} = k_{n+1} + 2 k_{n} , for all n 1 n\geq 1 , with k 1 = k 2 = 1 k_1 = k_2 = 1 . The infinite sum, S = k 1 7 1 + k 2 7 2 + k 3 7 3 S = \frac{k_1}{7 ^1} + \frac{k_2}{7 ^2} + \frac{k_3}{7 ^3} \ldots , is a fraction of the form a b \frac{a}{b} , where a a and b b are coprime integers. What is the value of a + b a+b ?


The answer is 47.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

16 solutions

Jau Tung Chan
May 20, 2014

Since S = k 1 5 1 + k 2 5 2 + k 3 5 3 + k 4 5 4 + . . . S=\frac{k_1}{5^1}+\frac{k_2}{5^2}+\frac{k_3}{5^3}+\frac{k_4}{5^4}+... , we have the following:

(1) 2 S = 2 k 1 5 1 + 2 k 2 5 2 + 2 k 3 5 3 + 2 k 4 5 4 + . . . 2S=\qquad \qquad \quad \frac{2k_1}{5^1}+\frac{2k_2}{5^2}+\frac{2k_3}{5^3}+\frac{2k_4}{5^4}+...

(2) 5 S = k 1 + k 2 5 1 + k 3 5 2 + k 4 5 3 + . . . 5S= \quad \qquad k_1+\frac{k_2}{5^1}+\frac{k_3}{5^2}+\frac{k_4}{5^3}+...

(3) 25 S = 5 k 1 + k 2 + k 3 5 1 + k 4 5 2 + . . . 25S=5k_1+k_2+\frac{k_3}{5^1}+\frac{k_4}{5^2}+...

Hence, it is clear that 25 S 5 S 2 S = 5 k 1 + k 2 k 1 25S - 5S - 2S = 5k_1 + k_2 - k_1 , or 18 S = 5 18S = 5 so S = 5 18 S=\frac{5}{18} . Thus a + b = 23 a+b=23 .

Wei Liang Gan
May 20, 2014

The charactersitic equation of the recurrence relation is x 2 x 2 = ( x 2 ) ( x + 1 ) = 0 x^2-x-2=(x-2)(x+1)=0 with solutions 2 2 and 1 -1

Hence, k n = A 2 n + B ( 1 ) n k_n=A2^n+B(-1)^n for some constants A A and B B

For n = 1 n=1 , k 1 = 1 = 2 A B k_1=1=2A-B

For n = 2 n=2 , k 2 = 1 = 4 A + B k_2=1=4A+B

Solving for both equations, we get ( A , B ) = ( 1 3 , 1 3 ) (A,B)=(\frac{1}{3},-\frac{1}{3})

Therefore, k n = 1 3 ( 2 n ( 1 ) n ) k_n = \frac{1}{3}(2^n - (-1)^n)

S = i = 1 k i 5 i = 1 3 i = 1 2 i ( 1 ) i 5 i = 1 3 i = 1 ( 2 5 ) i ( 1 5 ) i S = \sum \limits_{i=1}^{\infty} \frac{k_i}{5^i} = \frac{1}{3} \sum \limits_{i=1}^{\infty} \frac{2^i - (-1)^i}{5^i} = \frac{1}{3} \sum \limits_{i=1}^{\infty} (\frac{2}{5})^i - (-\frac{1}{5})^i

= 1 3 ( 2 5 1 2 5 1 5 1 ( 1 5 ) ) = 1 3 ( 2 3 ( 1 6 ) ) = 5 18 =\frac{1}{3}(\frac{\frac{2}{5}}{1-\frac{2}{5}}-\frac{-\frac{1}{5}}{1-(-\frac{1}{5})}) = \frac{1}{3}(\frac{2}{3}-(-\frac{1}{6})) = \frac{5}{18}

I'm slightly surprised that most of the solutions used the identity k n = 2 n + ( 1 ) n 3 k_n = \frac {2^n + (-1)^n}{3} to split the numerator into a true geometric progression.

Calvin Lin Staff - 7 years ago
Kumar Ashutosh
May 20, 2014

Here the sequence can be written as 1 , 1 , 3 , 5 , 11 , 21 , 43 , 85 , 171....... 1, 1, 3, 5, 11, 21, 43, 85, 171 ....... .So, S = 1 5 1 + 1 5 2 + 3 5 3 + 5 5 4 + 11 5 5 . . . . . S = \frac {1}{5^1} + \frac {1}{5^2} + \frac {3}{5^3} + \frac {5}{5^4} + \frac {11}{5^5} ..... . Now we have to express it as a Geometric Progression to find sum to infinite terms. We observe that every second number is one less than the twice the number preceding it and every number on odd places is one more than twice the number preceding it. So, we separate the numbers on odd places and even places. Let S 1 , S 2 S_1, S_2 denote sum of odd and even places respectively. So, S 1 = 1 5 1 + 3 5 3 + 11 5 5 . . . . . . . . . . . . . S_1 = \frac {1}{5^1} + \frac {3}{5^3} + \frac {11}{5^5} ............. and S 2 = 1 5 2 + 5 5 4 + 21 5 6 . . . . . . . . . . . . . S_2 = \frac {1}{5^2} + \frac {5}{5^4} + \frac {21}{5^6} ............. Let us first compute S 1 S_1 . We intend to make it a GP. So we can rewrite S 1 S_1 as S 1 = ( 1 5 1 + 2 5 3 + 8 5 5 + 32 5 7 . . . . . ) + ( 0 5 1 + 1 5 3 + 3 5 5 + 11 5 7 . . . . . . . ) S_1 = ( \frac {1}{5^1} + \frac {2}{5^3} + \frac {8}{5^5} + \frac {32}{5^7} ..... ) + ( \frac {0}{5^1} + \frac {1}{5^3} + \frac {3}{5^5} + \frac {11}{5^7} .......) = ( 1 5 1 + 2 5 3 + 8 5 5 + 32 5 7 . . . . . ) + 1 5 2 ( 1 5 1 + 3 5 3 + 11 5 5 . . . . . . . ) = ( \frac {1}{5^1} + \frac {2}{5^3} + \frac {8}{5^5} + \frac {32}{5^7} ..... ) + \frac {1}{5^2}( \frac {1}{5^1} + \frac {3}{5^3} + \frac {11}{5^5} .......) = ( 1 5 1 + 2 5 3 + 8 5 5 + 32 5 7 . . . . . ) + 1 5 2 ( S 1 ) = ( \frac {1}{5^1} + \frac {2}{5^3} + \frac {8}{5^5} + \frac {32}{5^7} ..... ) + \frac {1}{5^2}( S_1 ) = ( 1 5 1 + 2 5 3 + 8 5 5 + 32 5 7 . . . . . ) + 1 5 2 ( ( 1 5 1 + 2 5 3 + 8 5 5 + 32 5 7 . . . . . ) + 1 5 2 ( S 1 ) ) = ( \frac {1}{5^1} + \frac {2}{5^3} + \frac {8}{5^5} + \frac {32}{5^7} ..... ) + \frac {1}{5^2}( ( \frac {1}{5^1} + \frac {2}{5^3} + \frac {8}{5^5} + \frac {32}{5^7} ..... ) +\frac {1}{5^2}( S_1 ) ) . This becomes a GP with first term ( 1 5 1 + 2 5 3 + 8 5 5 + 32 5 7 . . . . . ) ( \frac {1}{5^1} + \frac {2}{5^3} + \frac {8}{5^5} + \frac {32}{5^7} ..... ) and common ratio 1 5 2 \frac {1}{5^2} . Sum of infinite terms of GP= a 1 r \frac {a}{1 - r} where a is first term and r is common ratio. Now let us first compute ( 1 5 1 + 2 5 3 + 8 5 5 + 32 5 7 . . . . . ) ( \frac {1}{5^1} + \frac {2}{5^3} + \frac {8}{5^5} + \frac {32}{5^7} ..... ) . Here apart from 1 5 1 \frac {1}{5^1} other numbers are in GP with first term 2 5 3 \frac {2}{5^3} and ratio 5 5 4 \frac {5}{5^4} . So ( 1 5 1 + 2 5 3 + 8 5 5 + 32 5 7 . . . . . ) ( \frac {1}{5^1} + \frac {2}{5^3} + \frac {8}{5^5} + \frac {32}{5^7} ..... ) = 1 5 + 2 5 3 1 4 5 2 \frac {1}{5} + \frac { \frac {2}{5^3}}{1 - \frac {4}{5^2}} = 23 105 \frac {23}{105} . So we have S 1 S_1 as a GP with first term 23 105 \frac {23}{105} and ratio 1 5 2 \frac {1}{5^2} . Therefore S 1 = 23 105 1 1 5 2 S_1 = \frac {\frac {23}{105}}{1 - \frac {1}{5^2}} = 115 504 = \frac {115}{504} .Now S 2 = 1 5 2 + 5 5 4 + 21 5 6 . . . . . . . . . . . . . S_2 = \frac {1}{5^2} + \frac {5}{5^4} + \frac {21}{5^6} ............. = ( 1 5 2 + 4 5 4 + 16 5 6 . . . . = ( \frac {1}{5^2} + \frac {4}{5^4} + \frac {16}{5^6} .... + 1 5 4 + 5 5 6 + 21 5 8 ) \frac {1}{5^4} + \frac {5}{5^6} + \frac {21}{5^8} ) = ( 1 5 2 + 4 5 4 + 16 5 6 . . . . = ( \frac {1}{5^2} + \frac {4}{5^4} + \frac {16}{5^6} .... + 1 5 2 ( 1 5 2 + 5 5 4 + 21 5 6 . . . ) \frac{1}{5^2}( \frac {1}{5^2} + \frac {5}{5^4} + \frac {21}{5^6}... ) = ( 1 5 2 + 4 5 4 + 16 5 6 . . . . = ( \frac {1}{5^2} + \frac {4}{5^4} + \frac {16}{5^6} .... + 1 5 2 ( S 2 ) \frac{1}{5^2}( S_2 ) . As in the case of S 1 S_1 this is also a GP with first term 1 5 2 + 4 5 4 + 16 5 6 . . . . \frac {1}{5^2} + \frac {4}{5^4} + \frac {16}{5^6} .... and common ratio 1 5 2 \frac {1}{5^2} . Now let us compute 1 5 2 + 4 5 4 + 16 5 6 . . . . \frac {1}{5^2} + \frac {4}{5^4} + \frac {16}{5^6} .... . This is a GP with first term 1 5 2 \frac {1}{5^2} and common ratio 4 5 2 \frac {4}{5^2} . Therefore 1 5 2 + 4 5 4 + 16 5 6 . . . . \frac {1}{5^2} + \frac {4}{5^4} + \frac {16}{5^6} .... = 1 5 2 1 4 5 2 = \frac {\frac {1}{5^2}}{1 - \frac {4}{5^2}} = 1 21 = \frac {1}{21} . So we have S 2 S_2 as a GP with first term 1 21 \frac {1}{21} and ratio 1 5 2 \frac {1}{5^2} . Therefore S 2 S_2 = 1 21 1 1 5 2 \frac {\frac {1}{21}}{1 - \frac {1}{5^2}} = 25 504 \frac {25}{504} . Therefore we have S S = S 1 + S 2 S_1 + S_2 = 115 504 + 25 504 \frac {115}{504} + \frac {25}{504} = 140 504 = 5 18 = \frac {140}{504} = \frac {5}{18} where 5 and 18 are co-prime. Hence the answer = 5 + 18 = 23 = 5 +18 = 23 which is the required answer.

Did it similarity

Akira Kato - 4 years, 11 months ago
Alan Chee
May 20, 2014

The characteristic equation for the recurrence relation is x 2 x 2 = 0 x^2 - x - 2 = 0 . Hence x = 2 x = 2 or x = 1 x = -1 . Therefore k n = a ( 2 n ) + b ( ( 1 ) n ) k_n = a(2^n) + b((-1)^n)

Since k 1 = k 2 = 1 k_1 = k_2 = 1 , we get a = 1 3 , b = 1 3 a = \frac{1}{3}, b = -\frac{1}{3} . Hence k n = 1 3 ( 2 n ) 1 3 ( ( 1 ) n ) k_n = \frac{1}{3}(2^n) - \frac{1}{3}((-1)^n) .

Hence we can proceed to find the infinite sum S S . Now S = n = 1 k n 5 n = n = 1 1 3 ( 2 n ) 1 3 ( ( 1 ) n ) 5 n \displaystyle{S = \sum_{n=1}^{\infty}{\frac{k_n}{5^n}} = \sum_{n=1}^{\infty}{\frac{\frac{1}{3}(2^n) - \frac{1}{3}((-1)^n)}{5^n}}} = 1 3 n = 1 ( 2 5 ) n 1 3 n = 1 ( 1 5 ) n \displaystyle{=\frac{1}{3}\sum_{n=1}^{\infty}\left (\frac{2}{5} \right )^n - \frac{1}{3}\sum_{n=1}^{\infty}\left (\frac{-1}{5} \right )^n} = 1 3 × 2 5 1 2 5 1 3 × 1 5 1 ( 1 5 ) \displaystyle{=\frac{1}{3}\times\frac{\frac{2}{5}}{1-\frac{2}{5}}-\frac{1}{3}\times\frac{-\frac{1}{5}}{1-(-\frac{1}{5})}} = 2 9 + 1 18 = 5 18 \displaystyle{=\frac{2}{9}+\frac{1}{18}}=\frac{5}{18} .

Hence a + b = 5 + 18 = 23 a + b = 5 + 18 = 23 .

Jp Delavin
May 20, 2014

For a second-order linear recurrence equation of the form k n = α k n 1 + β k n 2 k_n = \alpha k_{n-1} + \beta k_{n-2} and k 1 = k 2 = 1 k_1 = k_2 = 1 , the closed form for k n k_n is given by

k n = a n b ( 1 b ) b n a ( 1 b ) a b ( a b ) k_n = \frac{a^n b(1-b)-b^n a(1-b)}{ab(a-b)} ,

where a a and b b are the roots of the quadratic equation x 2 α x β = 0 x^2 - \alpha x - \beta = 0 .

Solving the quadratic equation x 2 x 2 = 0 x^2-x-2=0 will give us the roots 2 2 and 1 -1 .

Thus,

k n = 2 n ( 1 ) ( 1 ( 1 ) ) ( 1 ) n ( 2 ) ( 1 2 ) 2 ( 2 ) ( 2 ( 1 ) ) k_n=\frac{2^n (-1)(1-(-1))-(-1)^n (2)(1-2)}{2(-2)(2-(-1))}

k n = 2 n ( 1 ) n 3 k_n=\frac{2^n-(-1)^n}{3}

Given this formula for k n k_n , we can easily solve the sum of the series S = k 1 5 1 + k 2 5 2 + k 3 5 3 + . . . S=\frac{k_1}{5^1}+\frac{k_2}{5^2}+\frac{k_3}{5^3}+... .

S = 1 3 ( 2 1 ( 1 ) 1 5 1 + 2 2 ( 1 ) 2 5 2 + 2 3 ( 1 ) 3 5 3 + ) S=\frac{1}{3} \left( \frac{2^1-(-1)^1}{5^1}+\frac{2^2-(-1)^2}{5^2}+\frac{2^3-(-1)^3}{5^3}+… \right)

S = 1 3 ( 2 5 1 2 5 1 5 1 ( 1 5 ) ) S=\frac{1}{3} \left( \frac{\frac{2}{5}}{1-\frac{2}{5}}-\frac{\frac{-1}{5}}{1-\left(\frac{-1}{5}\right)} \right)

S = 5 18 S=\frac{5}{18}

Thus, the answer is 5 + 18 = 23 5+18=\boxed{23} .

Ryandk St
May 20, 2014

notice that k n + 2 = k n + 1 + 2 k n k_{n+2}=k_{n+1}+2k_{n} ,we just multi S S with 2 5 \frac{2}{5} ,then we get 2 5 S = 2 k 1 5 2 + 2 k 2 5 3 \frac{2}{5}S=\frac{2k_1}{5^2}+\frac{2k_2}{5^3}… .

now ignore the k 1 5 1 \frac{k_1}{5^1} in S S and add 2 5 S \frac{2}{5}S with S S ,we get 7 5 S = k 1 5 1 + k 3 5 2 + k 4 5 3 \frac{7}{5}S=\frac{k_1}{5^1}+\frac{k_3}{5^2}+\frac{k_4}{5^3}… . It's easy to see that k 3 5 2 + k 4 5 3 \frac{k_3}{5^2}+\frac{k_4}{5^3}… is a part of 5 S = k 1 + k 2 5 + k 3 5 2 + k 4 5 3 5S=k1+\frac{k_2}{5}+\frac{k_3}{5^2}+\frac{k_4}{5^3}… .

now we get a equation: 7 5 S = k 1 5 1 + 5 S k 1 k 2 5 \frac{7}{5}S=\frac{k_1}{5^1}+5S-k_1-\frac{k_2}{5} ,so 18 S 5 = 1 \frac{18S}{5}=1 , S = 5 18 S=\frac{5}{18} ,finally a + b = 23 a+b=23

Shourya Pandey
May 20, 2014

We first write the initial terms of the given series. They are 1,1,3,5,11,21,43,85,...

Observe that

1=1

1=1*2-1

3=1*4-1

5=1*8-3

11=1*16-5

k n k_n = 2 n 1 k n 1 2^{n-1}-k_{n-1}

Therefore,

S = i = 1 k n 5 n \displaystyle \sum_{i=1}^\infty\frac {k_n}{5^n}

S= i = 1 2 i 1 k i 1 5 i \displaystyle \sum_{i=1}^\infty\frac{2^{i-1}-k_{i-1}}{5^i}

where we consider k 0 k_0 to be 0 0 .

S= i = 1 2 i 1 5 i \displaystyle \sum_{i=1}^\infty\frac{2^{i-1}}{5^i} - i = 1 k i 1 5 i \displaystyle \sum_{i=1}^\infty\frac{k_{i-1}}{5^i}

S= i = 1 2 i 1 5 i \displaystyle \sum_{i=1}^\infty\frac{2^{i-1}}{5^i} - S 5 \frac{S}{5}

S = (A geometric Progression with first term 0.2 and common ratio 0.4) - S 5 \frac{S}{5}

6 S 5 \frac{6S}{5} = 0.2 1 0.4 \frac{0.2}{1-0.4}

or, S = 5 18 \frac{5}{18}

Therfore, the required answer is 23.

Note: The sum of a geometric progression with first term a a and common ratio r r is equal to a 1 r \frac{a}{1-r}

Matt Enlow
May 20, 2014

We can begin by looking for geometric sequences k n = k 0 r n k_n = k_0 \cdot r^n that follow the given recursive rule k n + 2 = k n + 1 + 2 k n k_{n+2}=k_{n+1}+2k_n .

For any such sequence, we have k 0 r n + 2 = k 0 r n + 1 + 2 k 0 r n k_0 r^{n+2}=k_0 r^{n+1} + 2k_0 r^n , or r n + 2 = r n + 1 + 2 r n r^{n+2}=r^{n+1}+2r^n . Dividing by r n r^n gives r 2 = r + 2 r^2=r+2 , the solutions to which are r = 2 , 1 r=2,-1 . So any geometric sequence with a common ratio of either 2 2 or 1 -1 will satisfy the recursive rule.

Let f n = 2 n f_n=2^n and g n = ( 1 ) n g_n=(-1)^n . Since these sequences individually satisfy the recursive rule, any linear combination thereof will do so as well. So we want to find values of a a and b b such that the sequence a f n + b g n a f_n+b g_n is identical to the sequence k n k_n as defined in the problem.

Since k 1 = k 2 = 1 k_1=k_2=1 , we need a f 1 + b g 1 = 1 a f_1+b g_1=1 and a f 2 + b g 2 = 1 a f_2+b g_2=1 . This becomes 2 a b = 1 2a-b=1 and 4 a + b = 1 4a+b=1 , the solutions to which are a = 1 3 a=\frac{1}{3} and b = 1 3 b=-\frac{1}{3} . So an explicit formula for for k n k_n is given by

k n = 1 3 2 n 1 3 ( 1 ) n k_n=\frac{1}{3}\cdot 2^n-\frac{1}{3}(-1)^n .

The desired infinite sum is

S = n = 1 k n 7 n = n = 1 ( 1 3 ( 2 7 ) n 1 3 ( 1 7 ) n ) S=\displaystyle \sum_{n=1}^\infty \frac{k_n}{7^n} = \sum_{n=1}^\infty \left(\frac{1}{3}\left(\frac{2}{7}\right)^n-\frac{1}{3}\left(-\frac{1}{7}\right)^n\right) .

This can be split into a difference of two convergent geometric series:

1 3 n = 1 ( 2 7 ) n 1 3 n = 1 ( 1 7 ) n = 1 3 ( 2 5 ) 1 3 ( 1 8 ) = 7 40 \displaystyle\frac{1}{3} \sum_{n=1}^\infty \left(\frac{2}{7}\right)^n - \frac{1}{3} \sum_{n=1}^\infty \left(-\frac{1}{7}\right)^n = \frac{1}{3}\left(\frac{2}{5}\right)-\frac{1}{3}\left(-\frac{1}{8}\right)=\frac{7}{40} .

So the answer is 7 + 40 = 47 7+40=47 .

Gabriel Singhal
May 20, 2014

S = k 1 / 7 + k 2 / 7 2 + S=k_1/7 + k_2/7^2 + \ldots . Let it be equation 1. Now we divide the whole equation by 7. The result is S / 7 = k 1 / 7 2 + k 2 / 7 3 + S/7=k_1/7^2 + k_2/7^3 +\ldots . Label this equation 2. Subtracting 2 from 1 we get 6 S / 7 = k 1 / 7 + ( k 2 k 1 ) / 7 2 + ( k 3 k 2 ) / 7 3 + 6S/7=k_1/7+(k_2-k_1)/7^2+(k_3-k_2)/7^3+ \ldots . 6 S / 7 = 1 / 7 + ( 2 k 1 / 7 3 + 2 k 2 / 7 4 + 6S/7=1/7+(2k_1/7^3+2k_2/7^4+\ldots ). Looking at the bracket part, we can write it in the form of S S as 2 S / 7 2 2S/7^2 .We get a single variable equation in S S , that is 6 S / 7 = 1 / 7 + 2 S / 7 2 6S/7=1/7+2S/7^2 . Now solving for S S gives S = 7 / 40 S=7/40 . Since we want a + b a+b , the answer is 7 + 40 = 49 7+40=49 .

When working with infinite sums, we must be a bit careful about how we do arithmetic. In the above question, the most common approach was similar to the one shown above. We multiply the the sequence S = k 1 7 + k 2 49 + S = \frac{k_1}{7} + \frac{k_2}{49} + \cdots by some value, subtract this from the original equation, and reduce the right hand side using the recurrence relation.

It is not always the case that with infinite sums we can add or subtract them in this manner. The reason we are allowed to do so in this instance is because all of the terms in the sum are positive, and we can show the series is bounded. To do this, we can show that k i < 3 i k_i < 3^i , and so \frac{k_1}{7^i} < \(\frac{3}{7}\right)^i , which means that the series is less than a geometric series with common ratio 3 7 < 1 \frac{3}{7} < 1 , so it must converge.

Calvin Lin Staff - 7 years ago
Tsi C
May 20, 2014

The recursion k n + 2 = k n + 1 + 2 k n k_{n+2}=k_{n+1}+2k_{n} has the characteristic equation m 2 m 2 = 0 m^2-m-2=0 which gives the solution k n = A 2 n + B ( 1 ) n k_n=A2^n+B(-1)^n for some constants A and B. Substituting the values of k for n=1 and n=2, we get an explicit solution to the recursion equation: k n = 2 n ( 1 ) n 3 k_n=\frac{2^n-(-1)^n}{3} . Hence, S is given by 1 3 \frac{1}{3} [ ( 2 7 + 2 2 7 2 + ) ( 1 7 + 1 2 7 2 1 7 3 + ) ] [(\frac{2}{7}+\frac{2^2}{7^2}+\ldots)-(\frac{-1}{7}+\frac{1^2}{7^2}-\frac{1}{7^3}+\ldots)] = 1 3 ( 2 5 + 1 8 ) = 7 40 \frac{1}{3}(\frac{2}{5}+\frac{1}{8})=\frac{7}{40} . Thus, the answer is 47 47 .

Karthik Tadinada
May 20, 2014

The key idea is to create a combination of S so that as many terms as possible cancel out.

We use the fact that k n + 2 k n + 1 2 k n = 0 k_{n+2} - k_{n+1} - 2 k_{n}=0 to cancel out most of the terms.

S = k 1 7 + k 2 7 2 + k 3 7 3 + k 4 7 4 + . . . S=\frac{k_1}{7}+\frac{k_2}{7^2}+\frac{k_3}{7^3}+\frac{k_4}{7^4}+...

S 7 = ( k 1 7 2 + k 2 7 3 + k 3 7 4 + . . . ) - \frac{S}{7} = - ( \frac{k_1}{7^2}+\frac{k_2}{7^3}+\frac{k_3}{7^4}+...)

2 S 7 2 = ( k 1 7 3 + k 2 7 4 + . . . ) - \frac{2S}{7^2} = -( \frac{k_1}{7^3}+\frac{k_2}{7^4}+...)

Adding up both sides we have 40 49 × S = 1 7 + 1 7 2 1 7 2 = 1 7 \frac{40}{49} \times S=\frac{1}{7} + \frac{1}{7^2} - \frac{1}{7^2}=\frac{1}{7}

S = 7 40 \therefore S=\frac{7}{40}

Karan Jhanwer
May 20, 2014

The series is 1/7,1/(7^2),3/(7^3),5/(7^4),11/(7^5),21/(7^6),43/(7^7),85/(7^8).......

We can split the above into two series: 1. 1/(7^1),3/(7^3),11/(7^5),43/(7^7)....... 2. 1/(7^2),5/(7^4),21/(7^6),85/(7^8).......

The sum of first series can be calculated in the following way:

S= 1/(7^1)+3/(7^3)+11/(7^5)+43/(7^7)+........

S*(1/(7^2))= 1/(7^3)+3/(7^5)+11/(7^7)+43/(7^9)+......

On subtracting the two equations we get,

S*(48/49)= 1/(7^1)+ 2/(7^3)+ 8/(7^5)+ 32/(7^7)+........

The above equation from the second term is a GP with first term as 2/(7^3) and common ratio as 4/(7^2). Thus we can find the sum for the above series and get S= (47x7)/(45x48)

Similarly, we can calculate the sum for the second series and get the sum= 49/(48x45)

On adding the above two series we get ((47x7)+ 49)/(48x45)= (54x7)/(45x48)= 7/40. Therefore, a+b=47

Elvin Gu
May 20, 2014

If S = \frac{k_1}{7^1} + \frac{k_2}{7^2} + ... , then by using the recursive definition, S = 0 S = 0 + k 1 7 1 + k 2 7 2 + k 2 7 3 + k 3 7 4 + k 4 7 5 + . . . +\frac{k_1}{7^1} + \frac{k_2}{7^2} + \frac{k_2}{7^3} + \frac{k_3}{7^4} + \frac{k_4}{7^5} + ...
+ 2 k 1 7 3 + 2 k 2 7 4 + 2 k 3 7 5 + . . . +\frac{2k_1}{7^3} + \frac{2k_2}{7^4} + \frac{2k_3}{7^5} + ... . By grouping, we get:
S = k 1 7 1 + k 2 7 2 + 2 k 1 7 3 + 9 7 ( k 2 7 3 + k 3 7 4 + k 4 7 5 + . . . ) S = \frac{k_1}{7^1}+\frac{k_2}{7^2}+\frac{2k_1}{7^3}+\frac{9}{7}(\frac{k_2}{7^3}+\frac{k_3}{7^4} + \frac{k_4}{7^5}+...) = 58 243 + 9 49 ( S 1 7 ) =\frac{58}{243} + \frac{9}{49}(S-\frac{1}{7}) . Putting S S on one side, we get S = 7 40 47 S = \frac{7}{40} \Rightarrow 47

Sam Song
May 20, 2014

2 S = 2 k 1 7 1 + 2 k 2 7 2 + 2S = \frac {2k_1}{7^1} + \frac {2k_2}{7^2} + \ldots

7 S = k 1 + k 2 7 1 + k 3 7 2 + 7S = k_1 + \frac {k_2}{7^1} + \frac {k_3}{7^2} + \ldots

Since k n + 2 = k n + 1 + k n k_{n+2} = k_{n+1} + k_n for all n 1 n \geq 1 ,

By adding, 9 S = k 1 + k 3 7 1 + k 4 7 2 + 9S = k_1 + \frac {k_3}{7^1} + \frac {k_4}{7^2} + \ldots = k 1 + 49 S 7 k 1 k 2 = k_1 + 49S - 7k_1 - k_2

Therefore, 40 S = 6 k 1 + k 2 = 7 S = 7 40 40S = 6k_1 + k_2 = 7 \Rightarrow S = \frac {7}{40}

Adams Koreas
May 20, 2014

First we solve the recurrence relation kn+2=kn+1 + 2 * kn, with k1=k2=1. Setting kn=a^n we get the characteristic equation: a^n+2 =a^n+1 + 2*a^n, which yields a^2-a-2=0. The roots are 2 and -1. That means that the solution of kn is: A1 * 2^n + A2 * (-1)^n . For n=1 and for n=2 we have the initial value 1, so we get that A1=1/3 and A2=-1/3. Setting bn=(kn/7)^n for n=1, 2, 3 … we get bn= 1/3 * (2/7)^n + 1/3 * (-1/7)^n . We want to calculate the infinite sum S=b1 + b2 + b3 + …. Since 2/7 + (2/7)^2 + (2/7)^ + … = 7/5 and (-1/7) + (-1/7)^2 + (-1/7) ^3 + (-1/7)^4 +… = -[ (1/7) + (1/7)^3 + (1/7)^5 +…] + [(1/7)^2 + (1/7)^4 + (1/7)^6 +…] = -7/48 + 1/48 = -6/48= -1/8 we finally get S=(1/3) * (2/5) + (-1/3) * (-1/8 ) =0.1750= 175/1000 =7/40=a/b, where a and b are co primes integers, so a+b=47.

Calvin Lin Staff
May 13, 2014

It is clear that all the k i k_i terms are positive, so k i k_i are increasing and thus k n + 2 = k n + 1 + 2 k n 3 k n + 1 k_{n+2} = k_{n+1}+2k_n \leq 3 k_{n+1} . It follows (by induction or otherwise) that 0 k i 3 i 0 \leq k_i \leq 3^i , hence the infinite sum converges to a value between 0 and 1 1 3 7 \frac {1}{1-\frac {3}{7}} . Since all terms are positive, we are allowed to rearrange the terms.

Let S S denote the infinite sum. Observe that

2 S = 2 7 1 + 2 7 2 + 6 7 3 + 7 S = 1 7 0 + 1 7 1 + 3 7 2 + 5 7 3 + 49 S = 1 7 1 + 1 7 0 + 3 7 1 + 5 7 2 + 11 7 3 + \begin{array}{c}\ 2S & = & & \frac {2} {7 ^1} + & \frac {2} {7 ^2} +& \frac {6} {7 ^3} + & \ldots \\ 7S & = & \frac {1} {7^0} + & \frac {1} {7^1} + & \frac {3} {7^2} + & \frac {5} {7^3} + & \ldots \\ 49S & = \frac {1} {7 ^{-1} } + & \frac {1} {7 ^0} + & \frac {3} {7 ^1} + & \frac {5} {7 ^2} + & \frac {11} {7 ^3} + & \ldots \\ \end{array}

Hence 49 S 7 S 2 S = 7 49S - 7S - 2S =7 , or S = 7 40 S = \frac {7} {40} . Thus, a + b = 7 + 40 = 47 a+b=7+40=47 .

Note: Most students would not show that the sum S S is finite. However, this is necessary to justify the validity of the next step.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...